The Effect of Entrepreneurship Orientation on Family Business Performance in Pekanbaru with Family Involvement as Mediation - Richard Junius; Rodhiah Rodhiah (Budapest International Research and Critics University, 2022)
The purpose of this study is to examine the effect of entrepreneurial orientation on family business performance in Pekanbaru. To know the effect of entrepreneurial orientation on family involvement. To examine the effect of family involvement on family business performance. To examine the effect of entrepreneurial orientation on family business performance in Pekanbaru with family involvement as mediation. The number of samples used in this study were 135 respondents who are family business owners in Pekanbaru. This study used non-probability sampling with purposive sampling for the sample selection technique. The data collection technique used a questionnaire made in the form of a google form which was then distributed online. This study used SmartPLS for the data analysis technique. The results showed that entrepreneurial orientation had a positive effect on family business performance in Pekanbaru but not significant, entrepreneurial orientation had a positive effect on family involvement, family involvement had a positive effect on family business performance in Pekanbaru, and entrepreneurial orientation had a positive effect on family business performance in Pekanbaru when mediated by family involvement.